Cell Phone Application to Monitor Pain and Quality of Life in Neurogenic Pain Patients - Rachita Sood, MD, MPH; Jenna R. Stoehr, BA; Lindsay E. Janes, MD; Jason H. Ko, MD, MBA; Gregory A. Dumanian, MD; Sumanas W. Jordan, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2020)
Summary:. Management of postoperative pain is a challenge for healthcare providers in all surgical fields, especially in the context of the current opioid epidemic. We developed a cell phone application to monitor pain, medication use, and relevant quality of life domains (eg, mood, mobility, return to work, and sleep) in patients with neurogenic pain, including those with limb loss. A literature review was conducted to define application length and design parameters. The final application includes 12 questions for patients with limb loss and 8 for patients with neurogenic pain without limb loss. Pilot testing with 21 participants demonstrates acceptable time to complete the application (mean = 158 seconds, SD = 81 seconds) and usability, based on the mHealth App Usability Questionnaire. We aim for our application to serve as an outcome measure for evaluation of an evolving group of peripheral nerve procedures, including targeted muscle reinnervation. In addition, the application could be adapted for clinical use in patients undergoing these procedures for neurogenic pain and thus serve as a tool to monitor and manage pain medication use.